Pain Perception in Healthy Young Men Is Modified by Time‐Of‐Day and Is Modality Dependent. Issue 6 (28th December 2014) - Aviram, Joshua; Shochat, Tamar; Pud, Dorit
Abstract Objective Several physiological processes exhibit 24‐hour oscillations termed circadian rhythms. Despite numerous investigations on the circadian dynamics of pain perception, findings related to this issue remain inconsistent. This study aimed to assess the effect of time‐of‐day on multimodal experimental pain perception in healthy males, including "static" and "dynamic" quantitative sensory tests. Design A random order tests were performed in the morning, afternoon and evening. Subjects Forty‐eight healthy males (25.9 ± 4.7 years old). Methods Three different pain modalities i) mechanical (pain threshold, tolerance, and intensity), ii) heat (pain threshold and intensity), iii) cold (pain threshold measured in °C and in seconds and cold pain tolerance and intensity) utilizing nine "static" pain parameters, and two "dynamic" pain paradigms i) temporal summation and ii) conditioned pain modulation were assessed in each session. Results Pain scores varied significantly in six pain parameters during the day. Specifically, lower pain scores were found in the morning for cold pain threshold (in seconds and in °C), cold pain intensity, cold pain tolerance, heat pain threshold and intensity. There were no significant diurnal differences in the mechanical evoked pain parameters or in either of the "dynamic" pain paradigms. Conclusions Thermal pain scores varies during the day and morning seems to be the time‐of‐day most insensitive to pain. Also, dynamic tests and the mechanical pain model are not appropriate for detecting diurnal variability in pain. The results of this study may be partially explained by a potential analgesic effect of some hormones known to have diurnal variation (e.g., melatonin and cortisol).